Glutathione peroxidase 4 functional variant rs713041 modulates the risk for cardiovascular autonomic neuropathy in individuals with type 1 diabetes. (May 2019) - Admoni, Sharon Nina; Santos-Bezerra, Daniele Pereira; Perez, Ricardo Vesoni; Patente, Thiago Andrade; Monteiro, Maria Beatriz; Cavaleiro, Ana Mercedes; Parisi, Maria Candida; Moura Neto, Arnaldo; Pavin, Elizabeth Joao; Queiroz, Marcia Silva; Nery, Marcia; Correa-Giannella, Maria Lucia
Cardiac autonomic neuropathy is a neglected diabetic chronic complication for which genetic predictors are rarely reported. Oxidative stress is implicated in the pathogenesis of microvascular complications, and glutathione peroxidase 4 is involved in the detoxification of peroxides and of reactive oxygen species. Thus, the association of a functional variant in the gene encoding glutathione peroxidase 4 (rs713041) with this diabetic complication was investigated in 341 individuals with type 1 diabetes evaluated for cardiac autonomic neuropathy status (61.7% women, 34 [27–42] years old; diabetes duration: 21 [15–27] years; HbA1c: 8.3% [7.4–9.4]; as median [interquartile interval]). Cardiac autonomic neuropathy was present in 29% of the participants. There was an inverse association of the minor T allele of rs713041 with cardiac autonomic neuropathy (odds ratio = 0.39; 95% confidence interval = 0.17–0.90; p   =  0.0271) after adjustment for potential confounders. The functional glutathione peroxidase 4 variant rs713041 modulated the risk for cardiac autonomic neuropathy in the studied population with type 1 diabetes.